Tập trung hay đa dạng hóa danh mục cho vay? Bằng chứng từ một thị trường cận biên - Nguyễn Đức, Nguyên; Nguyễn Hoàng Nhật, Khanh; Trương Quang, Thái; Đặng Thu, Thủy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study explores the impacts of loan portfolio concentration (in loan terms, industries, sectors, and customers) on return as well as the risk of banks in a frontier market such as Vietnam. Using a fixed-effects model at the bank and time level for a sample of 32 commercial banks from Quarter IV/2003 to Quarter IV/2019, this study finds that loan portfolio concentration provides benefits for banks. More specifically, industrial concentration is positively related to bank return. In addition, concentration in loan terms is negatively associated with both credit risk and insolvency risk.